CLASSIFICATION OF ULTRABASIC ROCKS IN TERMS OF THE CHEMISTRY OF THEIR ROCK-FORMING FLUID SYSTEMS - Letnikov F.A.; Men'shagin Y.V. (My University, 1988)
Recent data on the distribution of fluid components in rocks of various composition and origin have led to theories of evolution of fluids in endogenous processes over the course of earth's history. The data indicate that variations in the chemical composition of rocks are to a certain degree related to changes in the fluids that accompanied their evolution. In order to elucidate this connection, the authors studied ultrabasic rocks of various genetic types. Factor and cluster analysis was used in the analysis. The calculations were run on a BESM-6 computer. The sample that we investigated consisted of analyses of rocks that had undergone practically no alternation by superimposed processes. All samples were statistically sound and reliable. Study methods and results are discussed.